2010
DOI: 10.1038/hr.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric features of short-term blood pressure variability

Abstract: Prolongations of cardiac cycles have a significantly larger contribution to short-term heart rate variability than shorteningsthis is called heart rate asymmetry. Our aim is to establish the existence of blood pressure asymmetry phenomenon, which has not been done so far. We used 30-min resting continuous recordings of finger pressure waveforms from 227 healthy young volunteers (19-31 years old; 97 female), and performed Poincaré plot analysis of systolic blood pressure (SBP) to quantify the effect. Median con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…33 Further, we have described another phenomenon of the asymmetry of systolic blood pressure variability in healthy people, and although short-term heart rate asymmetry was also present in the same persons there was no correlation between both phenomena. 35 Porta et al have reported that measures of heart rate asymmetry change according to the tilting angle during head-up tilting, that there is a significant difference in heart rate asymmetry expression between daily activity and night sleep, and that the expression of heart rate asymmetry develops with increasing age between the 16th and 40th weeks of gestation. 16, 36 Karamakar et al have shown that pharmacological autonomic modulation by atropine (parasympathetic blockade) or scopolamine (parasympathetic agitation) changes the expression of heart rate asymmetry; 37,38 that is, atropine reduces heart rate asymmetry, and scopolamine increases its expression.…”
Section: Discussionmentioning
confidence: 99%
“…33 Further, we have described another phenomenon of the asymmetry of systolic blood pressure variability in healthy people, and although short-term heart rate asymmetry was also present in the same persons there was no correlation between both phenomena. 35 Porta et al have reported that measures of heart rate asymmetry change according to the tilting angle during head-up tilting, that there is a significant difference in heart rate asymmetry expression between daily activity and night sleep, and that the expression of heart rate asymmetry develops with increasing age between the 16th and 40th weeks of gestation. 16, 36 Karamakar et al have shown that pharmacological autonomic modulation by atropine (parasympathetic blockade) or scopolamine (parasympathetic agitation) changes the expression of heart rate asymmetry; 37,38 that is, atropine reduces heart rate asymmetry, and scopolamine increases its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both definitions have been used with popular HRA indices namely Guzki's Index (GI), Porta's Index (PI) and Ehlers' Index (EI). HRA analysis has been reported to analyse asymmetric properties of short and long-term HRV [40,42], altered parasympathetic nervous system activity [43], severity of apnea [44], blood pressure variability [45] and cardiovascular dynamics [46]. There is no study done to look at HRA in fetal heart rates.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it has been proposed that this difference could be related to the rate 1719 , and the pattern of breathing 20 . Also by studying BPV, differences between rises and falls in systolic blood pressure have been identified 21 . Indeed, interbeat time series do not exhibit time reversal symmetry 22 — decelerations in original time series become accelerations in the series with the inverted temporal axis/time, and vice versa.…”
Section: Introductionmentioning
confidence: 99%